Analisa Course Scoring dari Kurikulum Prodi Teknik Listrik UNP - Meri Arnelis; Riki Mukhaiyar (Jurnal Pendidikan Teknik Elektro, 2020)
The Associate Degree Study Program of Electrical Engineering (PSTL) is a department at FT UNP whose aim is to produce graduates as professional workers in the electrical engineering field in accordance with the needs of the industrial world. In this study, researchers can find that the objectives of the PSTL have not been fulfilled because there are still many graduates who find it difficult to get a job because they do not get special competencies while in college. This study uses a descriptive qualitative method with an ex post facto approach focusing on comparative causal with closed questionnaire dissemination conducted to PSTL graduates who have worked in the industry. The research results obtained by researchers are that all courses in the Associate Expert program currently meet industry needs based on the distribution of questionnaires and references at the IQF level. However, the existing competencies in the PSTL curriculum have not been implemented well so that graduates find it difficult to get a job.